2008
DOI: 10.1128/mcb.01859-07
|View full text |Cite
|
Sign up to set email alerts
|

P-TEFb Is Critical for the Maturation of RNA Polymerase II into Productive Elongation In Vivo

Abstract: Positive transcription elongation factor b (P-TEFb) is the major metazoan RNA polymerase II (Pol II) carboxyl-terminal domain (CTD) Ser2 kinase, and its activity is believed to promote productive elongation and coupled RNA processing. Here, we demonstrate that P-TEFb is critical for the transition of Pol II into a mature transcription elongation complex in vivo. Within 3 min following P-TEFb inhibition, most polymerases were restricted to within 150 bp of the transcription initiation site of the active Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 77 publications
(127 reference statements)
6
135
0
1
Order By: Relevance
“…This step coincides with the initial RNAPII pausing event ∼30 nt downstream the transcriptional start. The initial pausing is also thought to be a checkpoint for the recruitment of CTD Ser2 kinases, such as P-TEFb, for RNAPII to enter the productive mode of transcriptional elongation [5,21]. In contrast to the capping enzymes, a large of number of RNA proteins (Table 1) implicated in RNA splicing and 3′ end formation bind to CTD in a Ser2 or Ser5/Ser2 phosphorylation dependent manner [22][23][24][25][26][27].…”
Section: Multiple Molecular Contacts To Facilitate Functional Couplingmentioning
confidence: 99%
“…This step coincides with the initial RNAPII pausing event ∼30 nt downstream the transcriptional start. The initial pausing is also thought to be a checkpoint for the recruitment of CTD Ser2 kinases, such as P-TEFb, for RNAPII to enter the productive mode of transcriptional elongation [5,21]. In contrast to the capping enzymes, a large of number of RNA proteins (Table 1) implicated in RNA splicing and 3′ end formation bind to CTD in a Ser2 or Ser5/Ser2 phosphorylation dependent manner [22][23][24][25][26][27].…”
Section: Multiple Molecular Contacts To Facilitate Functional Couplingmentioning
confidence: 99%
“…Initially, the transactivator Six4 recruits UTX to muscle-specific genes promoters, resulting in the demethylation of regulatory regions upstream the transcription start site; afterwards, removal of the repressive H3K27me3 mark within the coding region needs elongating RNA Polymerase II (RNA Pol II), established by pTEFIIb-dependent RNA Pol II phosphorylation. 135,136 Furthermore, recent studies demonstrated that the demethylation process is dependent on Spt6, a histone chaperone that destabilizes histone dimmer-tetramer nucleosomal contacts promoting transcriptional activation. Spt6 orchestrates H3K27 demethylation interacting with UTX and RNA Pol II at chromatin regions of muscle-specific genes, and it is required for appropriate muscle gene expression and myogenesis.…”
Section: Role Of Ezh2 In Skeletal Myogenesismentioning
confidence: 99%
“…It is presumed that HSF recruits factors that release paused Pol II and permit it to traverse the gene, although it is unclear which factors are direct targets and exactly how Pol II release occurs. p-TEFb plays an important role, because artificial recruitment bypasses the pause [57], and chemical inhibition blocks release from the pause [58]. It is likely that other activators (e.g.…”
Section: Regulating the Rate Of Transition By Proteins And Small Molementioning
confidence: 99%